The Effects of Three Bleaching Agents on Tooth Discoloration Caused by Mineral Trioxide Aggregate - Saati, Keyvan; Sheikhi, Sheida; Esnaashari, Ehsan; Valizadeh, Sara (Iranian Endodontic Journal, 2019)
Introduction: Successful outcome of pulp capping treatment using mineral trioxide aggregate (MTA), often leads to tooth discoloration. This study aimed to compare the efficacy of external bleaching technique with three bleaching agents naming hydrogen peroxide, carbamide peroxide and sodium perborate for correction of tooth discoloration caused by MTA. Methods and Materials: This in vitro, experimental study used 36 tooth blocks prepared from 12 bovine central incisors. White ProRoot MTA was applied in cavities; drilled in blocks for 40 days to cause discoloration. Then, the blocks were assigned to three experimental groups (n=12). Following application of hydrogen peroxide, carbamide peroxide and sodium perborate, the color parameters were determined at baseline and at 1, 7 and 14 days, using a spectrophotometer. Data were analyzed using repeated measure ANOVA and Tukey’s test. Results: No significant difference was noted in color change (∆E) immediately after bleaching with hydrogen peroxide and carbamide peroxide (P>0.05). However, these two groups had significant differences in ∆E with the sodium perborate group (P=0.001). Hydrogen peroxide group showed significantly higher ∆E at 1 week compared with other groups (P=0.01). The three groups were significantly different in ∆E at 2 weeks after bleaching (P=0.001). Pairwise comparisons revealed no significant difference between sodium perborate and carbamide peroxide in ∆E but they both had a significant difference with hydrogen peroxide (P=0.01). Conclusion: The three bleaching agents bleached the discoloured teeth effectively. Hydrogen peroxide had the highest efficacy whilst sodium perborate and carbamide peroxide had lower but similar efficacy. Keywords:Bleaching; Carbamide Peroxide; Hydrogen Peroxide; Mineral Trioxide Aggregate; Sodium Perborate